ECOLOGICAL COMPETENCE FORMATION OF THE FUTURE BIOLOGY TEACHERS AT THE FRAMES OF THE EDUCATIONAL COMPONENT "TEACHER'S ECOLOGICAL COMPETENCE" - M.V KHROLENKO (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2021)
The aim of the article is a research of the problem of ecological competence formation of the future biology teachers during professional training. The formation of environmental competence of future teachers is considered from the standpoint of the competency approach in synergetic combination with systemic, personality-oriented, activity, axiological, technological, contextual, reflective and coevolutionary-noosphere methodological approaches. It is emphasized that one of the important pedagogical conditions for the formation of this quality of students in the process of professional training is the use in this process of the potential of normative and selective disciplines of the cycle of professional training. On analysis basis of educational programs and syllabuses of higher education establishments of Ukraine, where future biology teachers are brought up, it has been found out that the cycle of professional training contains the educational components that are aimed at the formation of individual parts of ecological competence. However, most of the analysed syllabuses do not contain any academic discipline of ecological competence formation of a teacher. In this study we presented the educational component "Teacher's Ecological Competence", clarified its place in the structural-logical scheme regarding bachelor degree programs of secondary education, its role in ecological competence formation of the future biology teachers. The aim of the course is to form ecological competence of future teachers as an integrative characteristic, which is a systemic integrity of acquired ecological values, acquired ecological knowledge, ways of studying and researching phenomena, objects and processes of environment, realization of ecological education functions in professional activity. We concentrated on the aim and tasks of the educational discipline, highlighted general and professional abilities that a student is supposed to master during the learning of the mentioned course. Program learning outcomes, the structure of test credits, content modules, the content of lecture and practical courses, educational forms and methods were clarified and described during the research of this educational component.